Pediatric spinal glioblastoma of the conus medullaris: a case report of long survival - Antonella Cacchione; Angela Mastronuzzi; Maria Giuseppina Cefalo; Giovanna Stefania Colafati; Francesca Diomedi-Camassei; Michele Rizzi; Alessandro De Benedictis; Andrea Carai (Chinese Journal of Cancer, 2016)
Abstract High-grade gliomas of the spinal cord represent a rare entity in children. Their biology, behavior, and controversial treatment options have been discussed in a few pediatric cases. These tumors are associated with severe disability and poor prognosis. We report a case of a 4-year-old child diagnosed with an isolated glioblastoma multiforme of the conus medullaris. The patient underwent subtotal surgical excision, followed by adjuvant radiotherapy and oral chemotherapy. He is alive with mild neurologic deficits at 52 months after diagnosis. We describe the peculiar characteristics of this rare condition in pediatric oncology. We also provide an overview of current multidisciplinary therapeutic approaches and prognostic factors for this disease.